A two-stage fermentation process of erythritol production by yeast Y. lipolytica from molasses and glycerol. (December 2015) - Mirończuk, Aleksandra M.; Rakicka, Magdalena; Biegalska, Anna; Rymowicz, Waldemar; Dobrowolski, Adam
Highlights: The first study using industrial raw molasses and glycerol for erythritol production by Yarrowia lipolytica. New Y. lipolytica strains were achieved through genetic engineering. Molasses combined with glycerol promoted economical erythritol biosynthesis. Abstract: In this study, a two-stage fermentation process of erythritol production based on molasses and glycerol was investigated. During the first stage, the biomass of Yarrowia lipolytica was grown on medium containing sucrose as the sole carbon source. In the second stage, production of erythritol was initiated by glycerol addition. To use molasses as a substrate for erythritol synthesis, sucrose utilization was established by expressing the Saccharomyces cerevisiae SUC2 gene. In this study, cultivation of yeast Y. lipolytica could produce 52–114 g/L of erythritol. The productivity was 0.58–1.04 g/L/h, and yield was 0.26–0.57 g/g; the final biomasses yield ranged 17–41 g/L. This is the first report describing erythritol production via industrial raw molasses and glycerol by Y. lipolytica . This work uses genetically modified strains of Y. lipolytica as tool for the direct conversion of affordable raw industrial molasses and glycerol into the value-added erythritol product.